(untitled) (Revista Crioula, 2022)
This article seeks to reflect, from the hermeneutic perspective, the novel Capão Pecado, by Ferréz, aims to point out the contradictions and narrative duplicities made by the narrator. It is based on the analysis of the conception of “narrator”, according to Arrigucci Jr (1998), “violence”, as Chaui (2017) and Kehl’s reflections (1999) on the linguistic choices of the group Racionais Mc’s.